Cardiovascular risk in postmenopausal women - Pośnik-Urbańska, Aneta; Kawecka-Jaszcz, Kalina; Czarnecka, Danuta (Menopause Review/Przegląd Menopauzalny, 2008)
Cardiovascular diseases are the leading cause of mortality and morbidity not only in Poland, but also in Europe and the United States. Yearly 82,000 men and up to 91,000 women die from cardiovascular diseases, which makes up 43% of all-cause male and 55% of all-cause female mortality. Cardiovascular diseases are not only the most common cause of deaths in women, but also a constant increase of morbidity from cardiovascular diseases is observed, which can only partly be explained by the aging of the population. In recent years more attention has been devoted to the assessment of gender influence in the development of cardiovascular diseases. That is why in women special attention should be focused on cardiovascular risk factors such as hypertension, dyslipidaemia, and obesity, which directly increase the occurrence of cardiovascular complications, with the most common being stroke and myocardial infarction. Nowadays it is known that multidimensional knowledge about consequences and target organ damage of hypertension and other cardiovascular risk factors is necessary to reduce the real threat from cardiovascular diseases in women and improve the quality of their life.